Pengenalan Produk Olahan Ikan Kepada Siswa Siswi SD Negeri 03 Metro Pusat Sebagai Upaya Peningkatan Konsumsi Ikan - Ilham Wahyu Pamungkas; Desy Sasri Untari; Tri Adi Wibowo; Citra Puspitaningrum (BADAN PENERBIT STIEPARI PRESS, 2024)
Indonesia is a maritime country which has abundant potential for natural aquatic resources, one of which is fish which is used for human consumption, however the amount of fish consumption in Indonesia is very low. The low consumption of fish in Indonesia is caused by a lack of awareness among the public about the nutrition and benefits of fish, especially for children. In fact, fish consumption is believed to be able to complete nutritional needs and help the development and growth of children's brains and bodies, especially in improving intelligence and health for elementary school students. This is because fish contains nutrients such as protein, fatty acids, especially omega-3, vitamins and minerals. So, to increase fish consumption among children, especially elementary school students, it is necessary to take an approach by introducing delicious processed fish products to children so that children's consumption of fish increases. The aim of the community service activity is to socialize and introduce processed fish products to the community, especially to teachers and students at SDN 03 Metro Pusat. The results of the Community Service activities at SDN 03 Metro Utara were that 36 children liked processed fishery products and 4 children did not like them, this was due to the fishy aroma or odor in the products. The results of the analysis showed that 33 children knew information about fish-based fishery products such as nuggets, fish brains and fish meatballs, then 7 children did not know information about fishery product information.